Distribution of Tide Type in Indonesian Waters Based on 7 Days Data Measurement of Ipasoet-BIG Station - Muhammad Ramdhan; Yulius Yulius; Nindya Kania Oktaviana (Jurnal Segara, 2021)
Tidal data is needed in the field of energy, marine navigation, coastal construction and other activities related to the oceans. Tidal phenomena occur due to the interaction of the earth with space objects. The sea level rise in coastal waters can be modeled by a harmonic function containing tidal constant numbers. From the constants formed can be calculated a Formzahl number that shows the type of tides that occur at the observation station. This paper tries to describe the distribution pattern of tidal types that exist in Indonesian waters based on data observation collected at station belong to  the Geospatial Information Agency. The result is that there are 4 types of tides in Indonesian waters, with the most dominant distribution are  mixed tide, prevailing semi diurnal typel.